Banteay Chhmar : garrison-temple of the Khmer empire / Peter D. Sharrock ; with contributions by Claude Jacques, Swati Chemburkar, John Sanday, Julia Killmer ; colour photographs by Paisarn Piemmettawat - Sharrock, Peter D. (River Books, 2015)
As well as taking the visitor on a detailed tour of the monument, the book includes a new translation of the temple's main inscription, aligned with a contemporary inscription in neighboring Champa. This recounts the lost story of how the Cambodians marshalled their army in this temple, sending it from here to conquer Champa. The campaign is also reflected in a 'newsreel' of politico-military reliefs carved into the outer gallery of the temple, lavishly illustrated here for the first time. In addition, the story surrounding the unique series of Avalokiteshvara reliefs, their partial theft and recovery are also discussed.